Auditoría finaciera aplicada a la Cooperativa de Ahorro y Crédito "Pablo Muñoz Vega" sucursal ibarra período 2013, para determinar la razonabilidad de los estados financieros. - Capelo Aguilar, Patricia Elizabeth (2016)
This research is a management audit of the credit union "Pablo Muñoz Vega" Ltd., period 2013, was performed to achieve the purpose of the investigation was necessary to deepen the theory related to the object of study, the same as he fed on Generally Accepted Auditing Standards, Financial Audit conceptualisation, where he met the phases between the preliminary knowledge, evaluation of internal control system, Working Papers; Development of Findings and Report Writing and Communication of Results; audit methods used as questionnaires, observation; Internal Control System, and financial reasons, to indicate the level of management of the institution was raised. Upon completion of the work, based on the policies, procedures manuals, regulations, bylaws, Internal Control Instructions, provided by the cooperative. Ibarra agency finally an audit report containing weaknesses found during the execution of the audit of the financial period 2013, with their respective conclusion and recommendation, each of these routed to contribute to the institutional improvement as generated; the use of resources, strengthening weaknesses, better job performance, compliance with policies, standards and procedures. This research is structured as follows: Chapter I is the guiding framework containing, approach and formulation of the problem, objectives: general, specific and justification of the research. In Chapter II we discussed the theoretical framework within which we address the general and background research, comprising concepts and definitions related to the evaluation of the accounting process. Analysis of the results of the company's system of hypotheses, variables like its operationalization, dimensions, areas and indicators formula. In Chapter III Methodological Framework includes the Research Design, techniques and data collection instruments. Chapter IV Conclusions and Recommendations. In Chapter V the proposal is detailed the same it will help to fulfill the process.